Using biothesiometer, Neuropathy Symptom Score, and Neuropathy Disability Score for the early detection of peripheral neuropathy: a cross-sectional study - Mooi, Ching Siew; Lee, Kai Wei; Yusof Khan, Abdul Hanif Khan; Devaraj, Navin Kumar; Cheong, Ai Theng; Hoo, Fan Kee; Sulaiman, Wan Aliaa Wan; Loh, Wei Chao; Jian, Leong Yong; Hui, Teh Xian; Ramachandran, Vasudevan (Hamad Bin Khalifa University Press, 2024)
Patients with peripheral neuropathy could have damaged peripheral nerves, which leads to sensory and motor dysfunction. Diabetes, infections, and trauma are the major causes of peripheral neuropathy. Vibratory perception threshold (VPT) tools are commonly used to detect peripheral neuropathy. This study aims to determine the assessment of peripheral neuropathy through the different diagnostic tools in the community in Malaysia. A total number of 1283 participants were recruited from the seven retail pharmacies located in Selangor, Malaysia. The peripheral neuropathy test was conducted based on VPT tools on both feet using the digital biothesiometer. Following that, Neurological Symptom Score (NSS) and Neurological Disability Score (NDS) were taken from the participants to assess the neurological symptoms. Participants had an average age of 40.6 ± 12.9 years and were mostly of Chinese ethnicity (54.1%). The findings show that increasing age was associated with more severe peripheral neuropathy across the various assessment tools, but gender differences were found with the biothesiometer test and ethnicity has severity in the biothesiometer and disability scores. The sensitivity and specificity of the biothesiometer test were 0.63 and 0.84, respectively. The combined tool NSS and NDS had high specificity and a high positive predictive value, suggesting that it could be a reliable indicator of peripheral neuropathy when both scores are elevated. The findings show that the biothesiometer test, NSS, and NDS are considered screening VPT tools for diagnosing peripheral neuropathy. However, further evaluation and diagnostic testing are necessary in cases of a positive test result.